Studies on Modification of Surface Properties in Polycarbonate (PC) Film Induced by DC Glow Discharge Plasma - K. A. Vijayalakshmi; M. Mekala; C. P. Yoganand; K. Navaneetha Pandiyaraj (International Journal of Polymer Science)
The polycarbonate film (PC) surface was treated using glow discharge low-pressure air plasma. The modified surface was characterized by contact angle, FTIR, XRD, AFM, and XPS analysis. The surface-modified samples were further investigated using T-peel test for technical applications. The surface energy of the sample was estimated by measuring contact angle. The results show that, after plasma treatment, the root mean square (RMS) roughness of PC film was gradually increased with exposure time. Plasma treatment modified the chemical composition of the polymer surface and it made the surface to be highly hydrophilic. It was found that the air plasma treatment increases the polar component of PC film.